Sombreamento contínuo e intermitente e a resposta produtiva e bromatológica das forrageiras Megathyrsus maximus e Urochloa brizantha - Sergio Murilo Duarte (2018)
Forage plants when submitted to light restriction may present changes in their productivity and quality resulting from morphological and physiological changes necessary for adaptation to the growing environment. The objective of this study was to evaluate the interference of continuous and intermittent shading, with 70% light restriction, on the productivity, chemical composition and physiology of four tropical forages. Two experiments were conducted in a randomized completeblock design with 5 replicates, the first one in a 2 x 3 factorial scheme, with two forages (piatã grass and marandu grass) submitted to different light conditions (full sun, shading continuous and with three hours of sun). The second experiment was conducted with the same experimentaldesign, but with tamani grass and tanzania grass forages. In the first trial, the piatã grass presented a higher daily dry matter accumulation rate (40.9 kg ha-1 day-1) than the marandu grass (34.4 kg ha-1 day-1), regardless of the condition of luminosity in the cultivation environment,however, it was not observed a variation in the productivity between grass-size and tanzania grass. Continuous and intermittent shading with 70% light restriction resulted in a lower daily accumulation of dry matter, with reductions of 17.4, 28.5, 28.8 and 30.3% for tanzania, tamani,piatã and marandu, respectively compared to plants kept in full sun condition. On the other hand, in both trials, the protein content was higher in plants kept under shading compared to full sun. The NDF levels found in forage grasses, Tanzania grass, piatã grass and marandu grass grown in the full sun were higher than those observed for shaded environments. The forages studied when exposed to continuous shading show a significant reduction of the physiological variables,while in the intermittent shading the averages approach the values found in the full sun, in response to the momentary light stimulus. Tanzania grass is characterized by a higher photosynthetic rate in detriment to the Tamani grass, although the latter shows a greater adaptation to the shading. The changes in the physiological variables of the shaded forages exposed to the direct light stimulus of 3h studied are positive, but do not reflect in productive gains. The productive behavior and the bromatological composition of the four forages maintainedin continuous shading with sombrite are similar to those found with the environment with intermittent shading with 3h of direct sunlight, which validates the use of continuous shading with sombrite in simulation to naturally shaded environments.